Nickel Niobate Anodes for High Rate Lithium‐Ion Batteries. Issue 1 (14th November 2021) - Xia, Rui; Zhao, Kangning; Kuo, Liang‐Yin; Zhang, Lei; Cunha, Daniel M.; Wang, Yang; Huang, Sizhao; Zheng, Jie; Boukamp, Bernard; Kaghazchi, Payam; Sun, Congli; ten Elshof, Johan E.; et al.
Abstract: Fast charging is one of the key requirements for next‐generation lithium‐ion batteries, however, lithium‐ion diffusion rates of typical electrode materials are limited. Nanosizing of active electrode material is a common strategy to increase the effective lithium‐ion diffusion transport rate, but it also decreases the volumetric energy/power density and stability of the battery. In this work, nickel niobate NiNb2 O6 is demonstrated for the first time as a new intrinsic high‐rate anode material for lithium‐ion batteries without the requirement of realizing nano‐architectures. The NiNb2 O6 host crystal structure exhibits only a single type of channel for lithium‐ion intercalation and can be fully lithiated with a capacity of about 244 mAh g −1 at low current densities. Interestingly, a high diffusion coefficient of 10 −12 cm 2 s −1 at 300 K enables fast (dis)charging at high current densities resulting in high capacities of 140 and 50 mAh g −1 for 10 and 100C respectively. The minimal volume change during lithiation is the origin of the stable reversible lithiation process in NiNb2 O6 and leads to 81% capacity retention after 20 000 cycles at 100C. Finally, full cell systems against LiFePO4 and Li[Ni0.8 Co0.1 Mn0.1 ]O2 (NCM811) cathodes demonstrate the promising energy storage performance of nickel niobate anodes in practical battery devices. Abstract : Nickel niobate NiNb2 O6 is a new intrinsic high‐rate anode material and can be fully lithiated with a capacity of about 244 mAh g −1, while a high diffusion coefficient of 10 −12 cm 2 s −1 enables fast (dis)charging with capacities of 140 and 50 mAh g −1, for 10 and 100 C respectively, with 81% capacity retention after 20 000 cycles at 100 C.